The Role of University Education in Fostering Student Entrepreneurship: The Case of Durban University of Technology, South Africa - Nhleko, Mary-Ann Nokulunga; Karambakuwa, Joe Kumbirai; Ngibe, Musawenkosi (Contemporary Issues of Business and Management: The Proceedings of the \(10^{th}\) International Conference on Business and Management Dynamics (ICBMD), Edition 1, 2025)
South Africa faces challenges of economic sluggishness. Thus, the significant role and positive influence of entrepreneurship and the advancement of entrepreneurial culture in educational, economic and social expansion in South Africa cannot be underestimated. Due to higher unemployment rates constantly corroding job prospects, it is acknowledgeable to accept that entrepreneurship would be reflected as the succeeding career option, nevertheless, university alumni possess very slight attention to becoming entrepreneurs. The study aims to identify the role of university education in promoting entrepreneurship among students. Using mixed approach of qualitative and quantitative, the researcher collected information through the use of questionnaires and structured interviews with student entrepreneurs. A sample size of 253 was used. For structured interviews, a sample of 10 was used. Quantitative data were processed using SPSS Version 28, through graphs and tables. The results revealed that the approach to introducing graduates to the entrepreneurial mindset and the range of abilities required in the global labour market is to incorporate entrepreneurship education within the curriculum. The study revealed such an approach needs support from other government institutions. The study concluded that there was a significant relationship between entrepreneurship education and business success among alumni as it nurtured the foundation for networking and corroborations that contributed to the development of an entrepreneurial mindset.